A nomogram based on iron metabolism can help identify apathy in patients with Parkinson’s disease - Jiang-ting Li; Yi Qu; Hong-ling Gao; Jing-yi Li; Qi-xiong Qin; Dan-lei Wang; Jing-wei Zhao; Zhi-juan Mao; Zhe Min; Yong-jie Xiong; Zheng Xue (Frontiers in Aging Neuroscience, 2023)
BackgroundsApathy is common in Parkinson’s disease (PD) but difficult to identify. Growing evidence suggests that abnormal iron metabolism is associated with apathy in PD. We aimed to investigate the clinical features and iron metabolism of apathetic patients with PD, and construct a nomogram for predicting apathy in PD.MethodsData of 201 patients with PD were analyzed. Demographic data, Apathy Scale (AS) assessments, and serum iron metabolism parameters were obtained. Spearman correlations were used to assess relationships between AS scores and iron metabolism parameters, separately for male and female patients. Additionally, a nomograph for detecting apathetic patients with PD was built based on the results of logistic regression analysis.ResultsThe serum transferrin (TRF, p < 0.0024) concentration and total iron binding capacity (TIBC, p < 0.0024) were lower in the apathetic group after Bonferroni correction, and they were negatively associated with AS scores in male participants with PD (TRF, r = −0.27, p = 0.010; TIBC, r = −0.259, p = 0.014). The nomogram was developed by incorporating the following five parameters: age, sex, serum iron concentration, TIBC and Hamilton Depression Rating Scale (HAMD) scores, which showed good discrimination and calibration, with a consistency index of 0.799 (95% confidence interval = 0.732–0.865).ConclusionAbnormal iron metabolism may contribute to apathy in PD, especially among men. TIBC levels in combination with HAMD scores can be effectively used for the prediction of apathetic patients with PD.